The Anthropology of Epidemics - Kelly, Ann H.; Keck, Frédéric; Lynteris, Christos (Routledge Studies in Health and Medical Anthropology, 2019)
Over the past decades, infectious disease epidemics have come to increasingly pose major global health challenges to humanity. The Anthropology of Epidemics approaches epidemics as total social phenomena: processes and events which encompass and exercise a transformational impact on social life whilst at the same time functioning as catalysts of shifts and ruptures as regards human/non-human relations. Bearing a particular mark on subject areas and questions which have recently come to shape developments in anthropological thinking, the volume brings epidemics to the forefront of anthropological debate, as an exemplary arena for social scientific study and analysis.